Pengaruh Label Halal, Harga, Dan Brand Loyalty Terhadap Keputusan Pembelian Produk Indomie Pada Mahasiwa Muslim Kota Jambi - Dini Oktaviani; Agustina Mutia (ICONS: Islamic Economics Journal, 2025)
The purpose of this study is to determine the influence of halal labels, prices, and brand loyalty on the purchase decision of Indomie products in Muslim students in Jambi City. The number of samples in this study is 96 people and uses an incidental sampling technique, which is a sample determination technique based on chance, anyone who by chance or incidentally meets the researcher can be used as a sample if it meets the criteria, consumers who buy indomie and are willing to fill in the data from the author. Multiple linear regression analysis is used as a data analysis technique. The results of the study showed that halal labels and prices had a positive and significant effect on the purchase decision of indomie products in Jambi City Muslim students, while brand loyalty had no effect on the decision to purchase indomie products in Jambi City Muslim students. Based on the data analysis in this study, these variables are valid and reliable. In the classical assumption test, this study is normally distributed, heteroscedasticity does not occur, and multicollinearity occurs.